Improving Critical Thinking Skills and Natural Sciences Learning Achievement Through The Implementation of Problem-Based Learning Model at The IXA Grade of Junior High School 21 Semarang - Rachayuni, Rachayuni (FMIPA UNNES, 2020)
This study aimed to determine the effectiveness of the implementation of problem-based learning model to improve critical thinking skills and Natural Sciences learning achievement in soil material. This study was classroom action research. The subject of the study was students at the IXA grade of Junior High School 21 Semarang in the academic year of 2018-2019. This class action research was conducted into 2 cycles, each cycle had 2 meetings. The stages of each cycle consisted of planning, taking action (acting), observing the action (observing), and analyzing the data on the results of observing the action (reflecting). The data collection technique was written test, consisting of multiple-choice tests to measure cognitive aspects and description questions to measure critical thinking skills. The data analysis of this study was a comparative descriptive technique, followed by a critical analysis of comparative descriptive results by reflecting. The result of this study showed that the implementation of problem-based learning model can improve critical thinking skills and natural science learning achievement at the IXA grade of Junior High School 21 Semarang in the academic year of 2018-2019 in soil material. This can be seen from the achievement of critical thinking skills that have increased from pre-cycle, cycle 1 and cycle 2. The average result of critical thinking skills achieved in the pre-cycle was70.83, at the end of cycle 1 was 79.86, and at the end of cycle 2 was 86.76. The lowest value of critical thinking skills in the pre-cycle was 54.00, at the end of cycle 1 was 65.00, and at the end of cycle 2 was 73.00. The highest value of critical thinking skills in the pre-cycle was 80.00, at the end of cycle 1 was 87.00, and at the end of cycle 2 was 93.00. The cognitive aspect of learning achievement achieved in pre-cycle with the lowest value was 52.00, in cycle 1 was 60.00, and in cycle 2 increased to 68.00. The highest pre-cycle value was 88.00, cycle 1 was 92.00, then cycle 2 increased to 96.00. The average grade in the pre-cycle was 74.07, in cycle 1 increased to 79.72, and cycle 2 increased to 84.97. The number of students who scored at least 75 in the pre-cycle was 72.4%, cycle 1 was 79.3% and cycle 2 was 93.1%.